Analysis and survey of resource management on modern data center networks - ENGGang D; Zheng-hu GONG; Hong WANG; Lin CHEN; Zhi-hong LIU (Tongxin xuebao)
Data center is the basic facility of Internet and cloud computing. Since network resource is critical resource in data center thorough study and analysis of its management, which can help to improve data center's performance, save costs and expenses, and is of great significance. However, as the structure characteristic and application mode are pro-found changing, it brings tremendous challenges to modern data center network resource management. Currently, lots of studies have been made in this field. In order to have an overall perspective of current research, some of the most impor-tant aspects were summarized and analyzed, which are automatic address configuration, congestion control, network traf-fic management and virtualization management. They are also the hotspots in current academe. Based on the comprehen-sive comparison and analysis, some trends of the future data center network resource management were pointed out in the end.